Issues in developing speaking skills at tertiary level - Ravindran, S. (University of Jaffna, 2012)
The last few decades have witnessed the rise of English from its position as an International language, to that of global language: a medium through which people from all parts of the world can communicate with each other. A good command of English is a crucial benchmark for both professional competition and personal development. However, there has been an ongoing debate over the proficiency of the second language. Among the four basic skills of listening, speaking, reading and writing, speaking has received little attention, and is therefore the weakest. It is at the tertiary level that the ESL learners realize the importance and the need for developing speaking skills. Their need intensifies when seeking better jobs. There are various issues involved in the non development of the skill. In this study fifty eight second year students from the Faculty of Arts University of Jaffna were selected on a random basis. A qualitative method is used to collect data. Questionnaires were circulated to the students to gather data. Interviews were conducted with the staff and class room observation was utilized. Objectives of this study were to find the cause and remedies for the non development of the speaking skills and to facilitate the development of the speaking skills at the tertiary level. The causes and remedies for developing speaking skills of the second year students were found. The findings revealed the issues for the non development of the speaking skill of ESL learners.
Keywords: Issues in speaking skills; Tertiary level; Homogenous group ESL learners; ESL Learning